From Throat to Limb: A Novel Case of Compartment Syndrome Following Group A Streptococcal Pharyngitis - Simar Goyal; Justin Choy; Kendall Wermine; Sidart Pradeep; Khazeema Hafeez; Rusty Milhoan; Lavanya Srinivasan (Case Reports in Infectious Diseases)
Acute compartment syndrome is a medical emergency caused by increased pressure within a closed fascial space, leading to tissue ischemia and potential limb loss or death if untreated. While typically secondary to trauma, rare cases have been associated with streptococcal infections. However, no documented case exists of compartment syndrome originating from Group A Streptococcus (GAS) pharyngitis. We present a 35-year-old female, with prediabetes, who presented to the emergency department with worsening right lower extremity (RLE) pain and edema following a febrile illness with pharyngitis. Throat swab on admission and subsequent blood cultures tested positive for beta-hemolytic GAS. Despite initial management for sepsis and cellulitis with myositis, she developed compartment syndrome requiring urgent fasciotomy. Her postoperative course was complicated by hypotension, toxic shock-like syndrome, menorrhagia, and transaminitis, but she ultimately recovered with IV antibiotics and stepwise Jacob’s Ladder surgical wound closure. This report serves as the first known case of nontraumatic acute lower extremity compartment syndrome derived from disseminated GAS pharyngitis and may point to the development of novel virulence factor(s) for emerging strains of GAS in the United States. The case underscores the importance of recognizing GAS pharyngitis as a potential source of severe systemic infections, as early identification and aggressive management of invasive GAS infections may help prevent life-threatening complications.